Biochemical Changes Induced in Some Rabbit Tissues on the Administration of an Antimalaria Drug, Fansidar - Oloyede, O. I.; Asaolu, M. F. (Biological Sciences - PJSIR, 2005)
The effect of Fansidar (40 mg/kg), a widely used antimalaria drug, was investigated on enzyme activities and some other biochemical constituents in some selected rabbit tissues. The enzymes assayed were alanine transaminase, aspartate transaminase and alkaline phosphatase. Total protein and glucose contents in the tissues were also deter- mined. The results obtained showed a decrease in the activities of alanine transaminase and aspartate transaminase in liver and heart when the drug was administered. This indicates tissue damage, which was complicated with an increase in the activities of these enzymes in the blood due to cell leakage. There was a significant elevation of alkaline phosphatase activity in liver, heart and blood, on the third day of drug administration, which continued upto the seventh day only in the heart. This shows that prolonged usage of the antimalaria drug, Fansidar, may lead to cell destruction and degradation.